EFFECT OF INFORMATION USEFULNESS AND INFORMATION ADAPTION OF AVOSKIN PRODUCTS ON PURCHASE INTENTION - Dwi Ayu Lestari Pracoyo; Osa Omar Sharif (SEAN Institute, 2023)
This study aims to find out how much influence Electronic of Mouth (E-WOM) and its dimensions, namely information quality, information quantiity, information credibility, information usefulness, and information adoption on the interest in buying Avoskin skincare products on TikTok social media Researchers use quantitative methods with the purpose of this study, namely descriptive-causal. Data collection using non-probability sampling method with convience sampling type as much as 400 respondents user Avoskin. This study used questionnaire data collection techniques with ordinal scales and data analysis techniques using Partial Least Square Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software. Based on the results of data analysis, it can be concluded that information quality, information quantity and information credibility have a significant and positive effect on information usefulness. In addition, information usefulness has a positive and significant effect on information adoption. The information adoption variable has a positive and significant effect on purchase intention. The suggestions in this study are that the Avoskin company can maintain and improve the quality, quantity and credibility of information about Avoskin products on the TikTok social media platform so that it can increase consumer buying interest in Avoskin products.